Sole material for leisure shoes and preparation method thereof

The modified polysiloxane prepared by reacting polysiloxanes with hydroxyl groups, boric acid, diacid anhydride compounds and dibromoether compounds with hydroxyl groups, solved the problem of poor compatibility between polyborosiloxane and EVA, and achieved better blending and mechanical properties.

CN119912745AActive Publication Date: 2025-05-02WENZHOU YIFENG SHOES CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510421251.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-07
Publication Date
2025-05-02
Estimated Expiration
2045-04-07

AI Technical Summary

Technical Problem

Among the existing casual shoe sole materials, the compatibility of polyborsiloxane and EVA is poor, resulting in the compatibility effect of the compatibility agent becomes worse when the amount of polyborsiloxane is increased, and a modified material with good compatibility is urgently needed.

Method used

Modified polysiloxanes are prepared by reacting polysiloxanes, boric acid, diacid anhydride compounds and dibromoether compounds with end groups as hydroxyl groups, increasing ether bonds on the molecular chain and improving compatibility with EVA.

Benefits of technology

Without the use of compatible agents, the blending performance of modified polyborosiloxane and EVA is significantly improved, the melt index, fluidity and compatibility are better, and the mechanical properties are also improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a sole material for leisure shoes and a preparation method of the sole material. The sole material is prepared from the following components in parts by weight: 30-80 parts of EVA (Ethylene-Vinyl Acetate), 2-15 parts of modified polyborosiloxane, 5-20 parts of filler, 0.5-5 parts of a heat stabilizer, 0.2-5 parts of a zinc-containing compound, 0.5-10 parts of a foaming agent and 0.5-5 parts of a cross-linking agent, the modified polyborosiloxane is prepared from polysiloxane with hydroxyl as a terminal group, boric acid, a dianhydride compound and a dibromo ether compound through a reaction. According to the scheme, in the blending process of the modified polyborosiloxane and the EVA, the melt index is better, the fluidity is better, and the compatibility is better. And the mechanical property is also improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymers, and more particularly to a sole material for casual shoes. Background Art

[0002] In the prior art, most of the soles of casual shoes are made of EVA. In order to improve the performance, EVA and other materials are usually used for blending and modification. At present, polyborosiloxane is a strain rate sensitive intelligent material. It is a kind of organic silicon polymer material formed by adding B element into the Si-0-Si main chain of polysiloxane polymer. It has unique viscoelasticity, that is, the viscosity increases rapidly with the increase of shear rate. This extremely special fluid behavior gives polyborosiloxane excellent cushioning and shock absorption properties. As an excellent modified material, it is often used as a modification of EVA and blended with EVA. However, due to the poor compatibility of polyborosiloxane and EVA materials, it is often necessary to add a compatibilizer to provide its compatibility. However, as the amount of polyborosiloxane added increases, the compatibility effect brought by the compatibilizer will also deteriorate. Therefore, a modified material of EVA and polyborosiloxane with good compatibility is urgently needed as the sole material of casual shoes. Summary of the invention

[0003] In view of the shortcomings of the prior art, the object of the present invention is to provide a sole material for casual shoes.

[0004] To achieve the above object, the present invention provides the following technical solutions: A sole material for casual shoes, The composition comprises the following parts by weight: EVA: 30~80 parts Modified polyborosiloxane: 2~15 parts Filling: 5~20 parts Heat stabilizer: 0.5~5 parts Zinc compounds: 0.2~5 parts Foaming agent: 0.5~10 parts Cross-linking agent: 0.5~5 parts; The modified polyborosiloxane is prepared by reacting polysiloxane with hydroxyl terminal groups, boric acid, dianhydride compounds and dibromoether compounds.

[0005] As a further improvement of the present invention, The preparation method of the modified polyborosiloxane is as follows: Step 1: Take polysiloxane with hydroxyl end groups and heat it to 140°C, then add boric acid and heat it to 180°C, keep stirring, and react for 0.5h; Step 2: Cool down to 90°C, add triethylamine and dianhydride compounds, and keep stirring to react for 5 hours; Step 3: Raise the temperature to 150°C and react for 5 hours while stirring; Step 4: The temperature was lowered to 45° C., and then dibromoether compounds and catalysts were added and reacted for 6 hours to obtain modified polyborosiloxane.

[0006] As a further improvement of the present invention, The siloxane with hydroxyl end groups is dihydroxy-terminated polydimethylsiloxane.

[0007] As a further improvement of the present invention, The dianhydride compound is succinic anhydride.

[0008] As a further improvement of the present invention, The dibromoether compound is dibromodiethyl ether.

[0009] As a further improvement of the present invention, The catalyst is 1,1,3,3-tetramethylguanidine.

[0010] As a further improvement of the present invention, The boric acid is phenylboronic acid.

[0011] As a further improvement of the present invention, The mass ratio of the hydroxyl polysiloxane, boric acid, triethylamine, dianhydride compound, dibromoether compound and catalyst is 200-500:50-120:0.1-2:30-50:100-130:0.1-2.

[0012] As a further improvement of the present invention, The filler is calcium carbonate; The foaming agent is an AC foaming agent; The heat stabilizer is stearic acid; The zinc-containing compound is zinc stearate or zinc oxide; The cross-linking agent is DCP.

[0013] As a further improvement of the present invention, The preparation method is: Step A: Preheat the internal mixer to 80°C, set the speed to 40r / min, put EVA, modified polyborosiloxane, filler, heat stabilizer, and zinc-containing compound into the internal mixer for internal mixing and blending, add foaming agent and cross-linking agent when the internal mixer is heated to 120°C, continue to heat and stir until the temperature of the internal mixer rises to 125°C and discharge the material; Step B: The temperature of the double-roll mill is maintained at 90°C, the speed is maintained at 30 min / min, and the roller distance is maintained at 2 mm. The rubber material obtained in step A is added to the double-roll mill and triangularly packed for 5 to 10 times before being discharged into sheets. After being cooled to room temperature, the sheet is added to a crusher and crushed to obtain the sole material.

[0014] Traditional polyborosiloxane is prepared by reacting polysiloxane with hydroxyl end groups and boric acid, while the modified polyborosiloxane of the present application is prepared by reacting polysiloxane with hydroxyl end groups, boric acid, dianhydride compounds, and dibromoether compounds. First, polysiloxane with hydroxyl end groups and boric acid are polymerized. Due to the short polymerization time, the polymerization degree is incomplete, and the molecular chain still has hydroxyl groups. At this time, dianhydride compounds are added for polymerization, and triethylamine is added as a catalyst, especially succinic anhydride is used for ring opening, so that the hydroxyl groups on the main molecular chain can react with the anhydride, so that the other end of the molecular chain is a carboxyl group. At this time, dibromodiethyl ether is added, and 1,1,3,3-tetramethylguanidine is used as a catalyst. The bromine group can react with the carboxyl group, and dibromodiethyl ether has two bromines, which can play a bridging role, so that the molecular chain of polyborosiloxane has an ether bond. By increasing the ether bond, the compatibility of polyborosiloxane with EVA can be greatly improved, and the mechanical properties can also be improved to a certain extent. In particular, when phenylboric acid is selected as the boric acid, phenylboric acid is often used to polymerize polyborosiloxane due to its good mechanical properties, but the phenyl structure is often not compatible with EVA, resulting in poor performance of the final product. The modified polyborosiloxane prepared by the present invention makes up for this, and the performance is similar to or even better than that of the case where a compatibilizer is used without using a compatibilizer.

[0015] In the solution of the present invention, during the blending process of the modified polyborosiloxane and EVA, the melt index, fluidity and compatibility are better, and the mechanical properties are also improved. DETAILED DESCRIPTION

[0016] Example 1: Preparation of modified polyborosiloxane Step 1: Take dihydroxy-terminated polydimethylsiloxane (hydroxyl content 9.2%) and heat it to 140°C, then add phenylboric acid and heat it to 180°C, keep stirring, and react for 0.5h; Step 2: Cool down to 90℃, add triethylamine and succinic anhydride, and keep stirring to react for 5h; Step 3: Raise the temperature to 150°C and react for 5 hours while stirring; Step 4: The temperature was lowered to 45° C., dibromodiethyl ether and 1,1,3,3-tetramethylguanidine were added and reacted for 6 hours to obtain modified polyborosiloxane.

[0017] The mass ratio of each raw material is: Hydroxyl-terminated polydimethylsiloxane (hydroxyl content 9.2%): 200 parts Phenylboric acid: 100 parts; Triethylamine: 0.5 parts; Succinic anhydride: 40 parts; Dibromodiethyl ether: 90 parts; 1,1,3,3-Tetramethylguanidine: 0.5 parts.

[0018] Example 2: The sole material for casual shoes is prepared Weigh the materials according to the following weight parts: EVA (7470M): 60 copies Modified polyborosiloxane prepared in Example 1: 10 parts Calcium carbonate: 5 parts; Stearic acid: 1 part; Zinc stearate: 1 part; Zinc oxide: 2 parts; AC foaming agent: 3 parts; DCP cross-linking agent: 1 part; The preparation method is: Step A: Preheat the internal mixer to 80°C, set the speed to 40r / min, put EVA, modified polyborosiloxane, calcium carbonate, stearic acid, zinc stearate and zinc oxide into the internal mixer for internal mixing and blending, add AC foaming agent and DCP cross-linking agent when the internal mixer is heated to 120°C, continue heating and stirring until the temperature of the internal mixer rises to 125°C and discharge the material; Step B: The temperature of the double-roll mill is maintained at 90°C, the speed is maintained at 30 min / min, and the roller distance is maintained at 2 mm. The rubber material obtained in step A is added to the double-roll mill and triangularly packed for 5 to 10 times before being discharged into sheets. After being cooled to room temperature, the sheet is added to a crusher and crushed to obtain the sole material.

[0019] Comparative Example 1: Preparation of polyborosiloxane Take dihydroxy-terminated polydimethylsiloxane (hydroxyl content 9.2%) and heat it to 140°C, then add phenylboric acid and heat it to 180°C, keep stirring, and react for 2h to obtain polyborosiloxane. The mass ratio of each raw material is: Hydroxyl-terminated polydimethylsiloxane (hydroxyl content 9.2%): 200 parts Phenylboronic acid: 100 parts.

[0020] Comparative Example 2: EVA (7470M): 60 copies Modified polyborosiloxane prepared in Comparative Example 1: 10 parts Calcium carbonate: 5 parts; Stearic acid: 1 part; Zinc stearate: 1 part; Zinc oxide: 2 parts; AC foaming agent: 3 parts; DCP cross-linking agent: 1 part; The preparation method is: Step A: Preheat the internal mixer to 80°C, set the speed to 40r / min, put EVA, polyborosiloxane, calcium carbonate, stearic acid, zinc stearate and zinc oxide into the internal mixer for internal mixing, add AC foaming agent and DCP cross-linking agent when the internal mixer is heated to 120°C, continue heating and stirring until the temperature of the internal mixer rises to 125°C and discharge; Step B: The temperature of the double-roll mill is maintained at 90°C, the speed is maintained at 30 min / min, and the roller distance is maintained at 2 mm. The rubber material obtained in step A is added to the double-roll mill and triangularly packed for 5 to 10 times before being discharged into sheets. After being cooled to room temperature, the sheet is added to a crusher and crushed to obtain the sole material.

[0021] Comparative Example 3: EVA (7470M): 60 copies Modified polyborosiloxane prepared in Comparative Example 1: 10 parts Silane coupling agent Si-75 (compatibility agent): 0.8 parts Calcium carbonate: 5 parts; Stearic acid: 1 part; Zinc stearate: 1 part; Zinc oxide: 2 parts; AC foaming agent: 3 parts; DCP cross-linking agent: 1 part; The preparation method is: Step A: Preheat the internal mixer to 80°C, set the speed to 40r / min, put EVA, polyborosiloxane, calcium carbonate, stearic acid, zinc stearate and zinc oxide into the internal mixer for internal mixing, add AC foaming agent and DCP cross-linking agent when the internal mixer is heated to 120°C, continue heating and stirring until the temperature of the internal mixer rises to 125°C and discharge; Step B: The temperature of the double-roll mill is maintained at 90°C, the speed is maintained at 30 min / min, and the roller distance is maintained at 2 mm. The rubber material obtained in step A is added to the double-roll mill and triangularly packed for 5 to 10 times before being discharged into sheets. After being cooled to room temperature, the sheet is added to a crusher and crushed to obtain the sole material.

[0022] Ingredients:

[0023] test: 1. Melt index test: refer to GB / T 3682-2000; 2. Impact performance test: refer to ASTM F1614-99, use weight (only rod weight), half weight (2.5 joules), full weight (5 joules) to simulate the three states of walking, jogging and running. The sampling frequency during impact is 6000Hz.

[0024] (1) Maximum acceleration (G) refers to the peak acceleration when the hammer impacts the foam material. It is calculated based on the peak impact force (Fmax) / falling hammer mass (m) measured by the instrument. The value represents the shock absorbing capacity of the midsole material. The smaller the value, the better the cushioning and shock absorbing performance of the midsole material.

[0025] (2) Total impact time (DT) refers to the total time of impact and rebound of the hammer head in the process of impacting the foam material. The value can well reflect the instantaneous rebound characteristics of the midsole material during movement. The smaller the value, the shorter the time it takes for the midsole material to recover to its initial state after being subjected to force.

[0026] (3) Energy return (ER), which indicates the percentage of impact energy utilized in rebound during the impact process.

[0027] The materials obtained in Example 2, Comparative Example 2 and Comparative Example 3 were prepared into samples to be tested, and the specific preparation method was as follows: Molding foaming: Keep the upper and lower mold temperatures of the flat vulcanizer at 185°C, weigh 220g of masterbatch and put it into the mold, close the mold, and hold the pressure at 10MPa for 11 minutes. Get the semi-finished foam test piece. After the test piece is cooled, peel off the upper and lower skins, cut it into a test piece with a thickness of 18.75mm according to the compression ratio of 1.5 (1.5x12.5=18.75), and perform secondary molding to obtain a test piece with a thickness of 12.5mm.

[0028]

[0029] After adding the modified polyborosiloxane prepared in Example 1, the melt index of Example 2 is much better than that of Comparative Example 2 in which ordinary polyborosiloxane is added without adding a compatibilizer, and is not much different from that of Comparative Example 3 in which a compatibilizer and ordinary polyborosiloxane are added, which shows that the modified polyborosiloxane prepared in the present invention has better compatibility. In the impact performance test, Example 2 is also better than Comparative Examples 2 and 3. Traditional polyborosiloxane is prepared by reacting polysiloxane with hydroxyl end groups and boric acid, while the modified polyborosiloxane of the present application is prepared by reacting polysiloxane with hydroxyl end groups, boric acid, dianhydride compounds, and dibromoether compounds. First, polysiloxane with hydroxyl end groups and boric acid are polymerized. Due to the short polymerization time, the polymerization degree is incomplete, and the molecular chain still has hydroxyl groups. At this time, dianhydride compounds are added for polymerization, and triethylamine is added as a catalyst, especially succinic anhydride is used for ring opening, so that the hydroxyl groups on the main molecular chain can react with the anhydride, so that the other end of the molecular chain is a carboxyl group. At this time, dibromodiethyl ether is added, and 1,1,3,3-tetramethylguanidine is used as a catalyst. The bromine group can react with the carboxyl group, and dibromodiethyl ether has two bromines, which can play a bridging role, so that the molecular chain of polyborosiloxane has an ether bond. By increasing the ether bond, the compatibility of polyborosiloxane with EVA can be greatly improved, and the mechanical properties can also be improved to a certain extent. In particular, when phenylboric acid is selected as the boric acid, phenylboric acid is often used to polymerize polyborosiloxane due to its good mechanical properties, but the phenyl structure is often not compatible with EVA, resulting in poor performance of the final product. The modified polyborosiloxane prepared by the present invention makes up for this, and the performance is similar to or even better than that of the case where a compatibilizer is used without using a compatibilizer.

[0030] In the solution of the present invention, during the blending process of the modified polyborosiloxane and EVA, the melt index, fluidity and compatibility are better, and the mechanical properties are also improved.

[0031] As a specific implementation method of the improvement, In summary, The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A sole material for casual shoes, characterized in that: The composition comprises the following parts by weight: EVA: 30~80 parts Modified polyborosiloxane: 2~15 parts Filling: 5~20 parts Heat stabilizer: 0.5~5 parts Zinc compounds: 0.2~5 parts Foaming agent: 0.5~10 parts Cross-linking agent: 0.5~5 parts; The modified polyborosiloxane is prepared by reacting polysiloxane with hydroxyl terminal groups, boric acid, dianhydride compounds and dibromoether compounds.

2. The sole material for casual shoes according to claim 1, characterized in that: The preparation method of the modified polyborosiloxane is as follows: Step 1: Take polysiloxane with hydroxyl end groups and heat it to 140°C, then add boric acid and heat it to 180°C, keep stirring, and react for 0.5h; Step 2: Cool down to 90°C, add triethylamine and dianhydride compounds, and keep stirring to react for 5 hours; Step 3: Raise the temperature to 150°C and react for 5 hours while stirring; Step 4: The temperature is lowered to 45° C., a dibromoether compound and a catalyst are added and reacted for 6 hours to obtain modified polyborosiloxane.

3. A sole material for casual shoes according to claim 2, characterized in that: The siloxane with hydroxyl end groups is dihydroxy-terminated polydimethylsiloxane.

4. The sole material for casual shoes according to claim 2, characterized in that: The dianhydride compound is succinic anhydride.

5. The sole material for casual shoes according to claim 2, characterized in that: The dibromoether compound is dibromodiethyl ether.

6. The sole material for casual shoes according to claim 2, characterized in that: The catalyst is 1,1,3,3-tetramethylguanidine.

7. The sole material for casual shoes according to claim 2, characterized in that: The boric acid is phenylboronic acid.

8. The sole material for casual shoes according to claim 2, characterized in that: The mass ratio of the hydroxyl polysiloxane, boric acid, triethylamine, dianhydride compound, dibromoether compound and catalyst is 200-500:50-120:0.1-2:30-50:80-130:0.1-2.

9. The sole material for casual shoes according to claim 1, characterized in that: The filler is calcium carbonate; The foaming agent is an AC foaming agent; The heat stabilizer is stearic acid; The zinc-containing compound is zinc stearate or zinc oxide; The cross-linking agent is DCP.

10. A method for preparing a sole material for casual shoes according to any one of claims 1 to 9, characterized in that: The preparation method is: Step A: Preheat the internal mixer to 80°C, set the speed to 40r / min, put EVA, modified polyborosiloxane, filler, heat stabilizer, and zinc-containing compound into the internal mixer for internal mixing and blending, add foaming agent and cross-linking agent when the internal mixer is heated to 120°C, continue to heat and stir until the temperature of the internal mixer rises to 125°C and discharge the material; Step B: The temperature of the double-roll mill is maintained at 90°C, the speed is maintained at 30 min / min, and the roller distance is maintained at 2 mm. The rubber material obtained in step A is added to the double-roll mill and triangularly packed for 5 to 10 times before being discharged into sheets. After being cooled to room temperature, the sheet is added to a crusher and crushed to obtain the sole material.

Citation Information

Patent Citations

  • Degradable photoresponse polymer and preparation method thereof

    CN114773607A

  • Preparation method of modified EVA elastomer

    CN116284948A

  • Impact-absorbing and shock-absorbing foaming material with low glass transition temperature and preparation method of impact-absorbing and shock-absorbing foaming material

    CN118440429A

  • Method for Making a Thermo-Stable and Transparent Resin

    US20130144026A1

  • Disulfide-containing self-healing polymer blend

    WO2018108950A1